Effect of Respiratory Muscle Stretch Gymnastics Training on Peak Expiratory Flow Rate in Obese Female Subjects - Risha Kamble; Pratik Gamre; Shruti Tadmare; Shital Ghule; Gaurav Bhatnagar; Dikshant Poharkar (The Bioscan, 2025)
Background: Obesity is the condition in which excess body fat has accumulated which has negative impacts on the health of women in many ways. The prevalence of obesity ranges from 10-50% and morbid obesity affecting 5% of country's population. Many studies have found restrictive abnormalities associated with decreased breathing muscle strength and chest expansion. Respiratory muscle stretch gymnastics (RMSG) has been used as an additional form of rehabilitation for patients suffering from respiratory complications. RMSG is planned to reduce chest wall stiffness, particularly in the respiratory muscles of the chest wall. AIM: To assess the effects of Respiratory muscle stretch gymnastics training on peak expiratory flow rate in female obese subjects. Methodology: A total of 45 obese female subjects in age group of 20-40 years were selected according to the inclusion and the exclusion criteria. They were asked to perform RMSG exercises total 16 sessions spread over 4 weeks (4 days a week) 4 sets 3times. Pre and post peak expiratory flow rate were assessed on day one and 4th week of intervention by using peak expiratory flow meter. Result: Statistical analysis was done by using paired t test in which mean pretest score was 176.77 with standard deviation ±2.994 and mean post test score was 249.55 with standard deviation ±4.332. The statistical value of the paired t test was 15.636 with p value 0.00001 which is < 0.05 considered as significant. Conclusion: The study found significant improvement in PEFR among obese women following 4 weeks of RMSG training.